A performance-based approach to design reinforced-earth retaining walls. Issue 4 (August 2018) - Gaudio, D.; Masini, L.; Rampello, S.
Abstract: This paper describes a pseudo-static approach developed for geosynthetic-reinforced earth ( GRE ) retaining walls, calibrated against given levels of wall performance defined by specified values of earthquake-induced displacements. The GRE walls generally show a good performance under severe seismic loading due to the capability of reinforcements to redistribute the deformations induced by the seismic actions within the reinforced zone. This can be achieved by promoting the activation of internal plastic mechanisms involving the reinforcements strength, providing that they are characterised by adequate extensional ductility. In the proposed procedure, the seismic coefficient k to be used in a pseudo-static calculation is assumed equal to the internal seismic resistance of the wall k c int, related, through the kinematic theorem of limit analysis, to the maximum strength demand of geosynthetic reinforcements. The seismic coefficient is then calibrated against given levels of seismic wall performance, defined by threshold values of earthquake-induced displacements that result by the temporary activation of plastic mechanisms during severe seismic loading. Permanent displacements induced by earthquake loadings are evaluated through empirical relationships based on a parametric integration of a large number of Italian seismic records and are expressed as a function of the critical and the maximum horizontal accelerations. A procedure is finally proposed to conceive a reinforced-earth retaining wall with an internal seismic resistance lower than the external one, so that a prescribed level of seismic performance and the activation of internal mechanisms are ensured during severe seismic shaking.